Sosyal Medya Gazeteleri Nasıl Etkiliyor? Haberlerin Twıtter’Da Yayılması Üzerine Bir Araştırma - Sütçü, Cem S.; Bayrakçı, Serkan (The Turkish Online Journal of Design Art and Communication, 2014)
Social media has been an important outlet for newspapers. Social media have advantages in terms of reaching wider audience and sharing comments about news. Being a digital platform, modularity and automation make social media suitable for newspapers to disseminate their news. In social media there are very large amounts of data. Some of them are about news. To collect those data and analyze them to get meaningful information is a difficult task. Beside the software designed to be used for this purpose, it is possible to collect data with simple search tools like Twitter’s search function. Although automation very similar to manual data gathering is possible, data gathering is limited with this function. On the other hand, it is easy to use such functions and gives an idea on how complicated monitoring software work. In this work, by looking at the dispersion of news from different sections of newspapers on Twitter, the tweeting ratio of news were calculated. The relation of dissemination of news between newspapers and social media was examined. It is found that the higher the comment ratio on newspaper Website, the higher the dissemination of news on Twitter.
Keywords: Gazeteler; Sosyal Medya; Twitter; Newspapers; Social Media